2012
DOI: 10.12669/pjms.291.2619
|View full text |Cite
|
Sign up to set email alerts
|

The delayed management of main arterial injuries in extremity trauma: surgical challenges and outcomes

Abstract: Objective: To analyse the early outcome of main arterial injuries with delayed treatment in extremity trauma and help vascular surgeons in determining proper treatment strategy for such injuries. Methodology: Forty-three patients with delayed treatment of main arterial injuries during May 2003 and January 2008 were reviewed retrospectively. Results: In 43 patients, injuries were caused by blunt trauma in 26 cases and penetrating trauma in 17 cases. The maximum ischaemia time was 38 hours and the minimum was 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This is a typical and educational case that demonstrates the importance of the rapid diagnosis and multidisciplinary team approach to decrease the period of ischemia and the rate of amputation [1,4]. A limb ischemia greater than 6 h results in severe necrosis and amputation in up to 30% of patients [3,9]. Additionally, compartment syndrome is a major risk factor for amputation following artery injury; thus, fasciotomy done at the time of arterial repair lowers amputation rates [10,11].…”
Section: Discussionmentioning
confidence: 97%
“…This is a typical and educational case that demonstrates the importance of the rapid diagnosis and multidisciplinary team approach to decrease the period of ischemia and the rate of amputation [1,4]. A limb ischemia greater than 6 h results in severe necrosis and amputation in up to 30% of patients [3,9]. Additionally, compartment syndrome is a major risk factor for amputation following artery injury; thus, fasciotomy done at the time of arterial repair lowers amputation rates [10,11].…”
Section: Discussionmentioning
confidence: 97%
“…This emphasizes the need for frequent neurovascular checks in such patients, especially when multiple procedures are necessary. Delay in deterioration of vascular exam can take place over a period of time of variable length, ranging from several hours up to three weeks [ [6] , [7] , [8] ]. This indicates the need for close follow up and even outpatient screening after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…3 Many factors, such as the extent of soft tissue damage, the capacity of collaterals, pre-existing arterial disease, and the ischemia time may affect the clinical outcomes. 6 Mckenzie et al 7 found that the greatest impact on decision making between limb salvage and amputation depend on the severity of soft tissue injury. Prolonged ischemia is a well-recognized predictor of cell death, but the tolerance period varies between persons and depends on the severity of the ischemia and the presence of collateral flow.…”
Section: Discussionmentioning
confidence: 99%